Opposing actions of adrenal androgens and glucocorticoids on alternative splicing of Slo potassium channels in bovine chromaffin cells - Lai, Guey-Jen (The National Academy of Sciences, 2002)
Pituitary ablation (hypophysectomy) in rats was previously reported to cause a precipitous change in the relative abundance of two alternative splice variants of the “BK”- or “Maxi K”-encoding Slo gene in adrenal chromaffin cells. Inclusion of the optional “STREX” exon (STRess axis-regulated EXon) in a C-terminal splice site was reduced, in preference to the variant lacking an insert at this site. Adrenocorticotropic hormone (ACTH) injections prevented the drop in STREX inclusion, implicating stress-axis function, as opposed to other pituitary functions. Because ACTH promotes synthesis and release of glucocorticoids (corticosterone or cortisol, depending on species), we hypothesized that glucocorticoids applied directly would promote STREX inclusion. Contrary to predictions, we report that direct application of glucocorticoids to bovine cells in vitro decreased STREX inclusion. This effect was blocked by the glucocorticoid receptor antagonist RU38486. As with glucocorticoids, synthesis and release of the adrenal androgen dehydroepiandrosterone (DHEA) increases in response to stress or elevated ACTH levels in some species. We report that direct application of DHEA increased expression of the STREX variant in cultured bovine cells. Two other androgens, androstenedione and testosterone, had similar effects. We hypothesize that Slo splicing in adrenal chromaffin cells in vivo is differentially regulated by the integrative, concentration- and time-dependent actions of glucocorticoids and androgens, with potentially important ramifications for stress-evoked catecholamine secretion.